Electricity Peak Load Forecasting using CGP based Neuro Evolutionary Techniques. Issue 2 (3rd March 2016) - Khan, Gul Muhammad; Arshad, Rabia
Abstract: Proficient Economic and Financial planning is critical to the successful and efficient operation of power generating and distributing units. This planning becomes quite facile if the accurate and precise knowledge regarding the required power load is ascertained. This research is an innovative effort to bring forward different electric peak load forecasting models based on the Neuroevolutionary technique known as the Cartesian Genetic Programming Evolved Artificial Neural Network(CGPANN). Although CGPANN in itself is not novel but its application to power load forecasting is quite unique because of its innate ability to identify the best computationally efficient predictive model along with the recognition of the best appropriate features for load forecasting. Both the Feedforward and Recurrent CGPANN setups have been evolved here for peak load forecasting on a daily basis. The different setups developed have been trained and tested on the peak load data of United Kingdom National Grid. The models developed in this research have been tested and compared against previously proposed machine learning models. In comparison to contemporary models in the field, a more efficient and accurate peak load forecasting model has been produced using CGPANN based prediction methods.